Psychiatric Evidence in Criminal Trials: To Junk or Not to Junk? - Slobogin, Christopher (1998)
This Article begins, in Part I, with a brief review of the past four decades of psychiatric and psychological testimony in criminal trials (henceforth referred to simply as psychiatric testimony ). Although this review cannot be called comprehensive, it does make clear that, contrary to what the popular literature would have us believe, psychiatric innovation is neither at an all time high nor the prevalent form of opinion testimony by mental health professionals. At the same time, such nontraditional expert opinion from clinicians, on those rare occasions when it does occur, has changed over the past few decades in both content and objective. Part II canvasses historical developments in the law governing the admissibility of psychiatric testimony With the Supreme Court's recent decision in Daubert v. Merrell Dow Pharmaceuticals, this law has undergone a metamorphosis, at least on the surface. What is also clear, however, is that evidentiary changes have not, to date, affected the admissibility of most psychiatric testimony. Traditional psychiatric testimony continues to be admitted regardless of its reliability. Further, while novel psychiatric testimony is usually subjected to Daubert-type or other screening tests, the continuing ambiguity of these tests means that nontraditional evidence is still admitted, excluded, or limited in its scope for reasons that are not always immediately apparent. A better method of parsing out truly junk testimony is needed. Part III offers ways of improving the evidentiary analysis. A good framework for such analysis already exists-under the Federal Rules of Evidence, the admissibility of any expert testimony hinges on its materiality, probative value, helpfulness, and understandability.' Most courts, however, perhaps not attuned to the subtly different versions of behavioral science, could benefit from an elaboration of this framework as it applies to psychiatric testimony. The most important contention in Part III concerns the assessment of probative value. The thesis here is that a distinction should be made between psychiatric evidence presented to prove past mental state and psychiatric evidence proffered to prove acts. Given the difficulty, in theory and in practice, of proving past mental state,15 the reliability assessment that is part of gauging probative value should be less demanding for psychiatric evidence on this issue. At the same time, psychiatric testimony that focuses on whether an act occurred-an objective and scientifically verifiable fact-should have to meet a more stringent test. In short, assessment of probative value should take into account the extent to which accuracy is possible. Part III also makes suggestions aimed at improving analysis of the other three components of the admissibility framework: materiality, helpfulness, .and countervailing factors. First, courts should pay much closer attention to the substantive scope of the law governing mental state defenses, a move that should curtail some of the more outlandish claims. At the same time, the law should define the helpfulness inquiry in broad terms, focusing on the extent to which psychiatric evidence offers counterintuitive explanations. Finally, courts must consider whether the evidence will be subject to adversarial testing, given the importance of ensuring the evidence is understood for its actual worth. Part IV concludes the Article with a discussion of an interesting implication of the foregoing arguments: the ultimate impact of the proposed framework is to allow criminal defendants more leeway than the government in presenting psychiatric evidence. Part IV briefly presents two normative justifications for this outcome, the first derived from the constitutional right to present a defense and the second based on utilitarian concerns about what would happen if that right were seriously abridged. Taken together, the arguments made in this Article suggest that suspect psychiatric science has a role to play in the criminal courtroom, but normally only when it supports claims concerning the past mental state of a defendant